Ковальов В.В. Нові відомості про гастероміцети Національного природного парку «Гуцульщина» - Ковальов, В.В. (Харківський національний університет ім. В.Н. Каразіна, 2013)
New data on biodiversity of gasteroid Basidiomycota representatives of National Nature Park “Hutsulshchyna” (Ivano-Frankivs’k region, Ukraine) are presented. From 14 species, which were collected by us, five are registered for this Park for the first time and two species (Mutinus caninus and Mutinus ravenelii) are included in the Red List of Ukraine. Brief data about substrates and localities for all found species are presented.
Kovalyov V.V. New data about Gasteromycetes of National Nature Park "Hutsulshchyna"
Ковалёв В.В. Новые сведения о гастеромицетах Национального природного парка «Гуцульщина»
Keywords: Gasteromycetes; biodiversity; National Nature Park; Hutsulshchyna; Carpathians; Ukraine